Brolexikon - Gellerstam, Martin (Nordiske Studier i Leksikografi, 1995)
The Collins COBUILD English Language Dictionary (1987) introduced a new concept in lexicography in the shape of a new style of definition. A new step has now been taken in the direction of a bilingual dictionary based on this new type of definition, the so-called "bridge dictionary". These dictionaries - one of them has been published already - are meant to "bridge" the gap between monolingual and bilingual dictionaries by translating definitions. This will make it easier for the reader to use the dictionary, since definitions have been a stumbling-block for foreign readers. The bridge dictionary style of definition is discussed, especially the syntactic problems caused by mixing two languages. A new borderline between the languages is suggested by the author.